The Dialectical Nature of Economic Growth and Fiscal Decentralization: The Story of Pakistan - Ali, Basit; Iqbal, Abu Bakar (Journal of Developing Economies, 2022)
Purpose: This current study aims at finding a connection between fiscal decentralization and the growth of the economy in Pakistan. This paper looked at the different iterations of the National Finance Commission and Riesman award as the two attempts at the distribution of finances to the provinces from the federal government. Methodology: For the study, Ordinary Least Square (OLS) method with the Engel-Granger co-integration test was applied. Findings: The results showed that in the longer run, both the desired variables were significant i.e. the ratio of revenue by the provinces to federal revenue, and the transfer of revenue to the provinces was statistically significant and impact the economic growth positively. In the short-run model, the variable of transfer to provinces was statistically insignificant and did not favor decentralization, while the second variable ratio of tax revenue by the provinces to federal tax revenue was statistically significant. This shows that there is potential in the idea of monetary decentralization in Pakistan, but only if it is designed for the long run, not as a short-term fix. Recommendation: The analysis shows that decentralization shows a significant impact on economic growth in case of Pakistan and the research suggested that the policy should be design for long run rather than short run.